HIGH-ENERGY DIFFRACTION AND DUALITY RELATIONS - Jenkovszky, László; Szanyi, István (Одеські астрономічні публікації, 2017)
Relations between elastic and inelastic diﬀraction due to Regge factorisation and pomeron dominance are discussed in the light of the new phenomena discovered at the LHC in nearly forward scattering.